Dialogues between the Lma Iacia Qom and students of the Environmental Information Bachelor course of studies (Huellas, 2023)
This work reflects on an extension activity carried out by the students of the Environmental Information Bachelor course of studies and the Lma Iacia Qom native community of San Pedro, Buenos Aires province. Through this action, territorially-based intercultural extension activities were incorporated into the educational path of the degree program. The objective was to generate practices that foster the exchange of knowledge and reflection on how different ways of conceiving and experiencing the world have an impact on environmental configurations and the ways in which we appropriate the territory we inhabit. Additionally, we discuss the institutional and educational impact of this type of action, which may contribute to a comprehensive range of functions within possible curricular processes.
Keywords: Environmental Information Bachelor course of studies; ontological turn; Lma Iacia Qom native community; intercultural